De qui est-ce ? Médiapoétique d’un roman-surprise dans L’Express en 1955 - Marie-Ève Thérenty (Contextes)
In 1955, at the initiative of Françoise Giroud, L’Express offered its readers a curious competition. The aim was to find which of the following writers, François Mauriac, Françoise Sagan, André Maurois, Louise de Vilmorin, Roger Nimier, Paul Vialar, Henri Troyat and Béatrix Beck, had respectively written the various chapters of a detective novel, De qui est-ce? produced for the occasion. It turns out that, while this novel is apparently part of a long media genealogy that anchors it in the 19th century and in an elitist literary culture, it above all reveals L'Express's conversion to a commercial conception of literary value exemplified by the notion of the best seller. Logically, this move was accompanied by the weekly's conversion to the form of the newsmagazine, for which the novel De qui est-ce? was a significant announcement of the recipe: events, illustration, and editorialization.